2021
DOI: 10.2147/jpr.s295265
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effect of Lodenafil Carbonate in Rodent Models of Inflammatory Pain and Spinal Nerve Ligation-Induced Neuropathic Pain

Abstract: Introduction: New therapeutic alternatives for pain relief include the use of phosphodiesterase-5 (PDE5) inhibitors, which could prevent the transmission of painful stimuli by neuron hyperpolarization via nitric oxide (NO)/cyclic 3ʹ,5ʹ-guanosine monophosphate (cGMP) pathway. The present work investigated the antinociceptive activity of a new PDE5 inhibitor, lodenafil carbonate, in inflammatory and neuropathic pain models. Methods and Results: Although no effect was detected on neurogenic phase of formalin test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Different findings, using the EAE mouse models, showedthat the upregulation of GFAP [16,52] correlates with MS physiopathology. The increase in GFAP expression was also related to pain-like behaviors in a model of neuropathic pain induced by spinal cord ligation [53][54][55]. Here, we reported that the deletion of TRPA1 prevents the increase in GFAP+ve cells observed in the wild-type mice induced in the two different MS mouse models.…”
Section: Discussionmentioning
confidence: 67%
“…Different findings, using the EAE mouse models, showedthat the upregulation of GFAP [16,52] correlates with MS physiopathology. The increase in GFAP expression was also related to pain-like behaviors in a model of neuropathic pain induced by spinal cord ligation [53][54][55]. Here, we reported that the deletion of TRPA1 prevents the increase in GFAP+ve cells observed in the wild-type mice induced in the two different MS mouse models.…”
Section: Discussionmentioning
confidence: 67%
“…The analgesic effect of indomethacin, meloxicam, pregabalin, and their combinations on mechanical allodynia was also evaluated in the carrageenan-induced inflammatory pain model [ 35 , 36 ]. In brief, the baseline values of rats responding to mechanical stimuli were assessed before intraplantar injection of 20 μL of 2% carrageenan in the left hind paws.…”
Section: Methodsmentioning
confidence: 99%
“…Several animal studies have also proposed a beneficial pain-relieving effect of PDE5-Is in models of lesional [ 140 , 141 ] or metabolic neuropathic pain [ 142 ]. Sildenafil could ameliorate neuropathic pain symptoms in patients with diabetic peripheral neuropathy [ 143 ] and showed an antinociceptive effect in Sprague–Dawley male rats’ neuropathic pain models [ 144 ].…”
Section: Pde5 As a Drug Target For Disease Treatmentmentioning
confidence: 99%